2015
DOI: 10.1371/journal.pone.0139236
|View full text |Cite|
|
Sign up to set email alerts
|

Aureonitol, a Fungi-Derived Tetrahydrofuran, Inhibits Influenza Replication by Targeting Its Surface Glycoprotein Hemagglutinin

Abstract: The influenza virus causes acute respiratory infections, leading to high morbidity and mortality in groups of patients at higher risk. Antiviral drugs represent the first line of defense against influenza, both for seasonal infections and pandemic outbreaks. Two main classes of drugs against influenza are in clinical use: M2-channel blockers and neuraminidase inhibitors. Nevertheless, because influenza strains that are resistant to these antivirals have been described, the search for novel compounds with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…Aureonitol ( 95 ) is a tetrahydrofuran-containing natural product discovered in 1979 from Helichrysum aureonitens ( Figure 3F ). 24 A strategic decarboxylative dienylation of 94 delivers 95 in 32% yield with complete selectivity (>20:1 E/Z ) as controlled by the chemistry used to fashion the diene nucleophile. Application of this transformation simplifies the synthesis as 94 can be made in 7 simple steps from inexpensive (+)-xylose.…”
mentioning
confidence: 99%
“…Aureonitol ( 95 ) is a tetrahydrofuran-containing natural product discovered in 1979 from Helichrysum aureonitens ( Figure 3F ). 24 A strategic decarboxylative dienylation of 94 delivers 95 in 32% yield with complete selectivity (>20:1 E/Z ) as controlled by the chemistry used to fashion the diene nucleophile. Application of this transformation simplifies the synthesis as 94 can be made in 7 simple steps from inexpensive (+)-xylose.…”
mentioning
confidence: 99%
“…Oseltamivir carboxylate (100 − 3.2 µM) (OST-car; kindly donated by Hoffman-La Roche Inc., Basel, Switzerland) was used as a control. For influenza titration, the supernatants were harvested at 48 hpi, and the influenza virus was titrated by TCID50/mL using MDCK cells (5 × 104 cells/well in 96-well plates) through the Reed and Muench method ( Reed & Mounch, 1938 ; Sacramento et al, 2015 ). Non-linear regression of the dose response curves was performed to determine the 50% inhibitory effect on viral replication (EC 50 ) for the extracts and reference compound (OST-car).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a natural product derived from the fungus Chaetomium Kuntze ex Fries ( Chaetomiaceae ), aureonitol ( Figure 2 b), also shows effective inhibition against both IAV and IBV [ 38 ]. MOA studies demonstrated that aureonitol inhibits influenza hemagglutination and consequently impairs virus adsorption significantly [ 38 ].…”
Section: Small Molecule Inhibitors Targeting Ha Mediated Receptor Bindingmentioning
confidence: 99%
“…In addition, a natural product derived from the fungus Chaetomium Kuntze ex Fries ( Chaetomiaceae ), aureonitol ( Figure 2 b), also shows effective inhibition against both IAV and IBV [ 38 ]. MOA studies demonstrated that aureonitol inhibits influenza hemagglutination and consequently impairs virus adsorption significantly [ 38 ]. Molecular modeling studies suggested that aureonitol can fit well to the SA binding site of HA and interact with several highly conserved residues via hydrogen bonds [ 38 ].…”
Section: Small Molecule Inhibitors Targeting Ha Mediated Receptor Bindingmentioning
confidence: 99%